Multiple generalized xanthogranuloma in adult: Case report and treatment - Arun Achar; Biswanath Naskar; Prabodh Chandra Mondal; Mallika Pal (Wolters Kluwer Medknow Publications, 2011)
Xanthogranuloma is a benign, asymptomatic, and self-healing disorder of non-Langerhans cell histiocytosis, affecting mostly infants, children, and rarely adults. Diagnosis is easy in typical cases but become more complex in unusual forms. We report a case of a 28-year-old male patient who presented with multiple diffuse brown-to-yellowish papulonodular eruptions over extremities, ears, face, trunk, and extensors of joints with almost bilaterally symmetrical distribution for a period of one month. Histopathological examination of the skin biopsy specimen revealed features of xanthogranuloma. The patient was put on isotretinoin 20 mg once daily. Most of the lesions subsided or flattened within two months of isotretinoin therapy. This case is interesting because of the severity and atypical nature of the disease and also, the patient responded with isotretinoin therapy. But further study is required to observe the effectiveness of isotretinoin in xanthogranuloma.